The Association of Anxiety and Depression with the Quality of Life of Inflammatory Bowel Disease Patients - Simanjuntak, Tiroy Sari Bumi; K, Marcellus Simadibrata; Shatri, Hamzah; Abdullah, Murdani (The Indonesian Society for Digestive Endoscopy, 2025)
Background: Inflammatory Bowel Disease (IBD), which is chronic and often recurrent, causes psychological changes in patients. This puts IBD patients at a higher risk of developing various mental disorders, especially anxiety and depression. IBD patients who had symptoms of anxiety or depression tended to show a lower quality of life than patients without those symptoms.Methods: This research uses a cross-sectional design. Data collection was carried out using primary data obtained through interviews with IBD patients who were undergoing outpatient treatment from October to December 2023. Anxiety and depression were measured using the Hospital Anxiety Depression Scale (HADS) and quality of life for IBD patients was measured using the Inflammatory Bowel Disease Questionnaire 9 (IBDQ-9). These questionnaires have been translated into Indonesian and validated. The research sample is an accessible population that has passed the inclusion and exclusion criteria using unpaired numerical analytical sample calculations. The sample used in this research was 172 subjects.Results: In the multivariate analysis, after controlling for confounding variables, the fully adjusted prevalence ratio (PR) for anxiety symptoms was 1.182 (CI: 1.061–1.317, p = 0.002). Similarly, the fully adjusted PR for depression symptoms was 1.221 (CI: 1.075–1.386, p = 0.002).Conclusion: Anxiety and depression are more strongly associated with a decline in the quality of life of IBD patients based on the IBDQ-9 after controlling for confounding variables.Keywords: Anxiety, depression, IBD, quality of life